The relation of novel cardiovascular risk parameters in patients with familial Mediterranean fever. (January 2019) - Kozan, Mustafa; Ozan, Zeynep Tugba; Demir, Vahit; Ede, Hüseyin
Objective: In this study, we aimed at correlating the thickness of epicardial adipose tissue and levels of Vitamin D with cardiac risk in patients with familial Mediterranean fever. Methods: Sixty-five patients with familial Mediterranean fever and 38 healthy controls with matching age and sex were included in the study. The patients with a history of familial Mediterranean fever attacks within the previous two weeks or with any history of inflammatory or cardiovascular disease were excluded. Data regarding age, gender, weight, height, waist circumference, body mass index (calculated as weight/height 2 ), pulse wave velocity, serum Vitamin D levels from fasting blood samples, and Homeostatic Model Assessment for insulin resistance were obtained for the patients and controls. The epicardial adipose tissue was visualized as an echo-free space between the outer surface of myocardium and visceral pericardium using two-dimensional echocardiography, and the thickness of epicardial adipose tissue was measured in parasternal long-axis view at the end of diastole. Results: The patients with familial Mediterranean fever had significantly higher levels of C-reactive protein, epicardial adipose tissue, and pulse wave velocity (p < 0.001, <0.05, <0.005, respectively) as compared with the control group. However, the serum Vitamin D levels in the two groups were observed to be similar (p = 0.486). Weak but significant positive correlations were observed between epicardial adipose tissue thickness and C-reactive protein (r = 0.302, p < 0.005), epicardial adipose tissue thickness and pulse wave velocity (r = 0.263, p < 0.01), and C-reactive protein and pulse wave velocity (r = 0.235, p < 0.05). Conclusion: Thickness of epicardial adipose tissue and pulse wave velocity were observed to increase in patients with familial Mediterranean fever.